Antibacterial potential of Psidium guajava leaves extract at three different leaf ages toward gram-positive and gram negative bacteria / Nuramanina Mohd Zamzuri - Mohd Zamzuri, Nuramanina (2019)
The potential of natural substances for pharmaceutical purpose has long been the subject of investigation. The aim of this study is to compare the antibacterial potential of Psidium guajava leaves extract at three different leaf ages toward Gram-positive and Gram-negative bacteria. Three different leaf ages of P guajava which were young, middle and old were used in this study. The cultured Gram-negative and Gram-positive bacteria then were subjected to antibacterial analysis by disc diffusion method against two types of extracts which were water and ethanol extracts. The result showed that water extract of P. guajava at young age had highest mean zones of inhibition with value 22.67 ± 1.53 mm against Gram-negative bacteria. As conclusion, overall the ANOVA result showed that there were significance difference among all P. guajava leaves extract against Gram-positive and Gram-negative bacteria because the p value is lower than 0.05.